Implementasi Pembelajaran Berdiferensiasi untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa pada Materi Trigonometri - Safira Dhanesti; Ayu Wulandari, Andhika; Pardiastuti, Yuni (Universitas Veteran Bangun Nusantara, 2024)
Students have different backgrounds and characteristics. One way teachers meet the learning needs of students who have different characteristics is the application of differentiated learning. This study aims to identify the application of differentiated learning in improving students' mathematical comprehension abilities. This research implements differentiated learning on Trigonometry material to improve students' mathematical comprehension skills. This research is a Classroom Action Research (PTK) with four stages, namely planning, action, observation, and reflection. The subjects in this study were 35 class XI students with different abilities. The results of this study stated that there was an increase in the application of differentiated learning in the classroom after going through 2 cycles